AN ANALYSIS OF COMMISSIVE SPEECH ACT USED BY DANIEL FORESTER AS A MAIN CHARACTER IN THE TOMORROW WAR MOVIE BY CHRIS MCKAY - SOFENY, DANIAR; Farwati, Ruly Joan; Supriyatno, Supriyatno (JOEEL (Journal of English Education and Literature), 2023)
Commissive is a style of speech act in which the speaker expresses a willingness to do something in the future. This research was aimed to find the kinds of commisive speech acts used by Daniel Forester as the main character in The Tomorrow War movie in 2021 and to probe the functions of commisive speech act used. Descriptive qualitative research was applied in this research. The data were taken in the form of utterances that came from the main character who was Daniel Forester. The researchers used Austins and Searles theories to analyse the kinds of commisive speech acts and the functions of each kind. In this research, the researchers found some results (1) the entire data of commisive speech act in Daniel Forester, the main character in The Tomorrow War movie are 23 data included 6 kinds of commisive speech act, those are refusal, offer, promise, volunteer, threat, and guarantee. (2) Researchers have identified the functions of each data of the commisive speech act. In conclusion, the researchers have analysed Daniel Foresters utterances in The Tomorrow War movie and finds 6 kinds of commisive speech acts and their functions by using Austin and Searles theory.